Pulmonary Metastasectomy in Colorectal Cancer (PulMiCC) randomized controlled trial: a systematic review of published responses. (6th May 2022) - Williams, Norman R; Patrick, Hannah; Fiorentino, Francesca; Allen, Alexander; Sharma, Manuj; Milošević, Mišel; Macbeth, Fergus; Treasure, Tom
Abstract: OBJECTIVES: The objective of this review was to assess the nature and tone of the published responses to the Pulmonary Metastasectomy in Colorectal Cancer (PulMiCC) randomized controlled trial. METHODS: Published articles that cited the PulMiCC trial were identified from Clarivate Web of Science (©. Duplicates and self-citations were excluded and relevant text was extracted. Four independent researchers rated the extracts independently using agreed scales for the representativeness of trial data and the textual tone. The ratings were aggregated and summarized. Two PulMiCC authors carried out a thematic analysis of the extracts. RESULTS: Sixty-four citations were identified and relevant text was extracted and examined. The consensus rating for data inclusion was a median of 0.25 out of 6 (range 0–5.25, interquartile range 0–1.5) and, for textual tone, the median rating was 1.87 out of 6 (range 0–5.75, interquartile range 1–3.5). The majority of citations did not provide adequate representation of the PulMiCC data and the overall textual tone was dismissive. Although some were supportive, many discounted the findings because the trial closed early and was underpowered to show non-inferiority. Two misinterpreted the authors' conclusions but there was an acceptance that 5-year survival was much higher than widely assumed. CONCLUSIONS: Published comments reveal a widespread reluctance to consider seriously the results of a carefully conducted randomized trial. This may be because the results challenge accepted practice because of 'motivated reasoning', but there is a widespread misunderstanding of the fact that though PulMiCC with 93 patients was underpowered to test non-inferiority, it still provides reliable evidence to undermine the widespread belief in a major survival benefit from metastasectomy. Abstract : It ought to be remembered that there is nothing more difficult to take in hand, more perilous to conduct, or more uncertain in its success, than to take the lead in the introduction of a new order of things . .